implementasi program hafalan Al-Qur'an di SMP Islam Mbah Bolong Jombang - khoirun nisa'; Chusnul Chotimah (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
this school is classified as a private high school which has excellent programs as local content by implementing the Al-Qur’an memorization program. Each class must be able to achieve the memorization that has been determined by the school as a rote target. This study aims to (1) Know the implementation of local recitation program for memorizing Al-Qur’an (2) Knowing how the implementation and assessment of the Al-Qur’an memorization program in the school. The results of this study indicate that SMP Islamic Mbah Bolong Jombang has implemented a memorization program of the Al-Qur’an as a froom of implemtation of the local content curriculum aas well as the provision of the school founders. Learning outcomes in the froom of aral and written examination.